P4HB maintains Wnt-dependent stemness in glioblastoma stem cells as a precision therapeutic target and serum marker - Zheng Yuan; Hongbo Jing; Yilin Deng; Meichen Liu; Tao Jiang; Xiong Jin; Weiwei Lin; Yang Liu; Jinlong Yin (Oncogenesis)
Abstract Glioblastoma stem cells (GSCs) are pivotal in the recurrence and drug resistance of glioblastoma multiforme (GBM). However, precision therapeutic and diagnostic markers for GSCs have not been fully established. Here, using bioinformatics and experimental analysis, we identified P4HB, a protein disulfide isomerase, as a serum marker that maintains stemness in GSCs through the Wnt/β-catenin signaling pathway. Transcriptional silencing of P4HB induces apoptosis and diminishes stem cell-like characteristics in GSCs. Treatments with the chemical CCF624 or the China National Medical Products Administration (NMPA)-approved securinine significantly prolonged survival in patient-derived xenograft mouse models, underscoring P4HB’s potential as a therapeutic target and presenting an expedited path to clinical application through drug repurposing. Additionally, elevated P4HB levels in patient serum were found to correlate with disease progression, underscoring its utility as a biomarker and its promise for precision medicine.